Exploring the Alignment of 'Merdeka Belajar' with Nurcholish Madjid's Educational Philosophy: A Path to Inclusive and Independent Learning - Fadillah, Muhammad Aizri; Hirahmah, Atifah; Putri, Prima Isma; Andriyani, Dwi Rika; Mufit, Fatni (International Journal of Education, Information Technology, and Others, 2024)
This study employs a qualitative and descriptive approach using a library research method to explore Nurcholish Madjid's ideas on education, particularly concerning the concept of 'Merdeka Belajar,' and to identify its implications for the education system. The analysis focuses on how 'Merdeka Belajar' aligns with Madjid's educational philosophy and the potential impact of his ideas on its implementation. Primary data is derived from Madjid's works, which are analyzed to understand these aspects. The results indicate that 'Merdeka Belajar' aligns with Madjid's inclusivity, independence, and individual potential development principles. His views emphasize critical thinking, student autonomy, and inclusive education. This research provides new insights into the practical application of 'Merdeka Belajar' in creating a responsive and progressive educational environment consistent with Madjid's vision of inclusive and transformative education.